Role of Freight Forwarder In Import Export Business At PT.Jasa Trans Samudera Sulut - VINNITA LALOMA; Johny R. E. Tampi; Danny D. S. Mukuan (JURNAL ADMINISTRASI BISNIS, 2017)
Background This study was conducted at PT. Trans Samudera Sulut Service isone of the companies engaged in the service of the expedition which is usually calledfreight forwarder that serves the freight forwarder services in the form of cargo bothdomestically and abroad. The purpose of this research is to know how the role offreight forwarder in the implementation of import export business. The method ofresearch used in this study is using data analysis that takes place along with datacollection, such as data reduction, presentation and verification. In this research,Freight forwarder is a business entity that aims to provide services for all activitiesrequired for the implementation of the delivery, transport and receipt of goods byusing multimodal transport either by land, sea or air. The role of freight forwarder inthe import export business is the role in the consolidation of cargo, as the carrier, inthe documentation, in the packaging, in insurance. Result of this research then therole of freight forwarder in the implementation of import export business has beendone well although there may still be a few obstacles arises when import exportactivities take place as in the case of incompatibility between documents withchecked goods, weather factor effects and shipping facilities that have not used owncompanies such as aircraft and ships. Therefore, companies should pay more attentionto the roles of freight forwarders available at the time of export import. PT. TransSamudera Sulut Services also contribute in providing services to assist someentrepreneurs from North Sulawesi who use their services to facilitate the delivery ofgoods either outside or outside the country.Keywords: Role of Freight Forwarder, Export and Import